Automatic Writing in New Kurdish Poetry This research is a summary of a master's thesis entitled: (Automatic Writing in New Kurdish Poetry – Lower Kurdish Dialect), which was submitted to the Kurdish Department / College of Education and Language of Charmo University. - سەعدون, سامان عیزەدین; حسێن, سالار كەیم (Sulaimani Journal for Humanities, 2025)
The Summary of The Research which is called (Automatic Writing in Kurdish Modern Poetry) is an attempt to explain the genre of automatic writing in Kurdish poetry, this technique is one of the most important mechanism in the surrealism, the research is composed of two parts, the first part is theoretic in which we explained the historical backgrounds about the automatical expressions in old civilizations and then the analysis of those expressions by the modern terms, next we pointed out the similarities between automatic poetry and normal poetry. Then we specified the second part is about practicing automatic writing in modern Kurdish poetry, we mentioned the first attempt of composing modern Kurdish poetry in the seventies, and then we mentioned the progress of this type of poetry in the nineties, as for each phase we gave examples and analyses the poems according to the criteria and standards of automatic writing.